PREPARATION OF FE-DOPED ZINC OXYSULFIDE (Fe-Zn(O,S)) WITH SURFACE DEFECT FOR HYDROGEN EVOLUTION REACTION - Hardy Shuwanto; Jenni Lie; Hairus Abdullah; Subur P. Pasaribu (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
In this study, Fe-doped Zn(O,S) has been successfully fabricated by a one-step preparation process using chemical wet method. The Fe-doped Zn(O,S) photocatalysts were studied by varying the content of Fe dopant. The characterizations of Fe-doped Zn(O,S) were carried out by SEM and XRD analyses to determine the morphology and phase of samples. Furthermore, the optical and electrochemical properties were characterized through EIS, TPC, DRS and PL analyses. Briefly, Zn(O,S) with 5% Fe amount exhibited the most optimum condition as compared to other Fe amounts in which it showed better charge separation with the hydrogen evolution amount of 29000 mikromol/g in 10% EtOH solution. Lastly, the proposed mechanism is initially by the trapping of water molecules in the oxygen vacancy (defect) in Fe-Zn(O,S) sample followed by the reduction to generate hydrogen (H2) gas via the intermediate of proton (H+).